Experimental Study of the Boost Converter under Current Mode Control - Djamal Gozim; Kamel Guesmi; Djilali Mahi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents the practical analysis of Boost converter operating in continuous conduction mode under current control. We start by theconverter modeling, then experimental results will be exposed where we propose an experimental circuit, to study the influence of the variation of different circuit parameters such as reference current, input voltage and load. We also analyze the control technique performances. The experimental results are given and interpreted in each case.